SETUP OF THE TOPOGRAPHIC-CADASTRAL DOCUMENTATION CORRESPONDING TO THE CADASTRAL SECTOR NUMBER 108 FROM THE VILLAGE OF SĂLIȘTEA, ALBA COUNTY, IN VIEW OF LAND REGISTRATION (PANGEEA, 2025)
ABSTRACT: In order to prepare the cadastral technical documentation for land registration, several stages must be completed. This documentation is set up after field measurements have taken place, after data has been processed and the cadastral plan related to a cadastral sector from a territorial administrative unit (LAU) has been obtained.
Keywords: cadastral sector; local administrative units (LAUs)